Do Political Factors Affect Financial Performance in Public Sector? - Kamela, Hurian; Setyaningrum, Dyah (Riset Akuntansi dan Keuangan Indonesia, 2020)
Purpose: The implementation of regional autonomy in Indonesia has been regulated based on Laws of the Republic of Indonesia No 23 of the year 2014 concerning the responsibility given by the central government of the regional government to govern its own region. This is defined as regional autonomy. The government has appointed the members of Regional Legislative Councils (Dewan Perwakilan Rakyat Daerah - DPRD) to perform monitoring function on the regional government. There are several political factors which affect this monitoring function, one of which is due to the members of Regional Legislative Council originating from various parties. There is one component which makes up financial performance, which is the Locally-Generated Revenue (Pendapatan Asli Daerah - PAD). High locally-generated revenue gives us a clear description on a region’s success in improving its regional income and therefore being independent from the central government. In the year 2015, the compositition of the party supporting the regent / mayor was equal. Whereas in the year of 2016, the composition has changed, due to regional elections taking place on some cities or districts in Indonesia